2009
DOI: 10.1007/978-3-642-02181-7_2
|View full text |Cite
|
Sign up to set email alerts
|

An Extension of the Order Bound for AG Codes

Abstract: The most successful method to obtain lower bounds for the minimum distance of an algebraic geometric code is the order bound, which generalizes the Feng-Rao bound. We provide a significant extension of the bound that improves the order bounds by Beelen and by Duursma and Park. We include an exhaustive numerical comparison of the different bounds for 10168 two-point codes on the Suzuki curve of genus g = 124 over the field of 32 elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This is essential in order to attain the actual minimum distance of Hermitian two-point codes and in general greatly improves the order bound. The improved bounds d ABZ ′ , d DP [7] and d DK [6]…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is essential in order to attain the actual minimum distance of Hermitian two-point codes and in general greatly improves the order bound. The improved bounds d ABZ ′ , d DP [7] and d DK [6]…”
Section: Introductionmentioning
confidence: 98%
“…C Ω (D, G = 28P + 2Q) C Ω (D, G = 30P + 2Q) 9 9 9 10 10 10 The best bounds overall are the order bounds d DP [7] and d DK [6]. In the second part of the paper we present a framework to derive bounds of order type including the bounds d DP and d DK .…”
Section: Introductionmentioning
confidence: 99%
“…6] the equality between [27,28] and half the bound in [1]. This demonstrates that Andersen and Geil's bound [1] is much more convenient than [2,7,8] in some cases, though the former [1] is implied by the latter [2,7,8].…”
Section: Introductionmentioning
confidence: 96%
“…Finally, a result in a different direction was established in [21] where it was shown that for one-point algebraic geometric codes one can view Andersen and Geil's bound as a consequence of the Beelen bound [2] for more point codes and thereby also as a consequence of the Duursma-Kirov-Park bound [7,8] for such codes. However, it seems prohibitively difficult to prove the equality between the error correction capability of [27,28] and half the bounds in [2,7,8], while we proved in just a few lines [19,Prop. 6] the equality between [27,28] and half the bound in [1].…”
Section: Introductionmentioning
confidence: 99%
“…Esta cota mejora la cota de 56,54,52,51,48,46,44,43,42,41,40,39,38,36,35,34,33,32,31,30,29,28,28,26,25,24,23,22,21,20,21,18,19,16,17,16,13,12,14,10,13,8,12,10,9,8,8,6,8,7,4,5,…”
Section: Semigrupos Numéricosmentioning
confidence: 99%